2018
DOI: 10.1177/1077546318795527
|View full text |Cite
|
Sign up to set email alerts
|

Application of fuzzy dynamic weights drivability evaluation model in tip-in condition

Abstract: Only the subjective or objective method is employed to calculate the index weight in the evaluation of drivability, which makes the evaluation result less accurate. In this paper, a drivability evaluation model was proposed on the basis of fuzzy dynamic weights, and the drivability was evaluated in tip-in conditions. The evaluation indexes affecting drivability in tip-in conditions were determined using multi-dimensional analysis. The dynamic weight was built using an improved analytic hierarchy process and im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Tip-in condition is described as the process of rapid acceleration for the vehicle when the driver quickly triggers the accelerator pedal, and it is closely related to the transient characteristics of the vehicle. 25 When vehicle speed reaches the target speed (±5%), the accelerator pedal rapidly increases to the target opening within 0.2 s (greater than 30%) and it is maintained it for 3 s.…”
Section: Mixed Working Condition Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Tip-in condition is described as the process of rapid acceleration for the vehicle when the driver quickly triggers the accelerator pedal, and it is closely related to the transient characteristics of the vehicle. 25 When vehicle speed reaches the target speed (±5%), the accelerator pedal rapidly increases to the target opening within 0.2 s (greater than 30%) and it is maintained it for 3 s.…”
Section: Mixed Working Condition Identificationmentioning
confidence: 99%
“…However, the information redundancy between objective indicators has not been considered. For the objective scoring models and methods, 24 fuzzy analytic hierarchy process (FAHP), 25 gray relational analysis (GRA), 26 and FCE 21 have good subjective and objective consistency for a single working condition, but their accuracy is limited and the different working condition types have a great influence on its evaluation accuracy. Based on learning methods, BP neural network 27 and optimal extreme learning machine (OELM) 21 can improve the consistency of subjective and objective to 95%.…”
Section: Introductionmentioning
confidence: 99%
“…Especially in urban conditions, the driver is very sensitive to the comfort of gear selection performance because of the uninterrupted shifting action, which directly affects the driver's evaluation of a certain type of vehicle. [1][2][3] It can be said that as a user's perceptible item, the shifting performance of transmission is directly related to the degree of user complaints. Therefore, in order to meet the needs of consumers, automobile manufacturers need to improve the shifting quality and driving comfort as much as possible through continuous design optimization in the process of transmission development and matching.…”
Section: Introductionmentioning
confidence: 99%
“…The poor performance of manual transmission in automobile would reduce the driver's driving pleasure and make the driver feel tired. Especially in urban conditions, the driver is very sensitive to the comfort of gear selection performance because of the uninterrupted shifting action, which directly affects the driver's evaluation of a certain type of vehicle 1‐3 . It can be said that as a user's perceptible item, the shifting performance of transmission is directly related to the degree of user complaints.…”
Section: Introductionmentioning
confidence: 99%
“…The study concluded that vehicle body response was an indicator of comfort and did not find any actionable driveline dynamics that predicted subjective evaluation of the gearshift. Another study that uses their own metrics to evaluate the response to tip-in conditions was done in [79]. In this evaluation they took jury study results and compared the results with eight vehicle signals including; thumb rise rate, acceleration peak, response time, response delay, engine speed fluctuation, throttle change rate, kick, and jerk.…”
Section: Discussionmentioning
confidence: 99%